HUBUNGAN PERILAKU PENDERITA DIABETES MELLITUS DENGAN STATUS KEBERSIHAN GIGI DAN MULUT - Izzati, Rahmil; Reca (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
The background of this research is that oral hygiene is an important aspect of healthcare, especially for diabetes mellitus patients who are prone to oral complications. Diabetes mellitus, characterized by high blood sugar levels, can trigger bacterial growth and worsen oral hygiene. The problem is that the behavior of diabetes mellitus patients greatly affects their oral hygiene status, yet many diabetes mellitus patients exhibit inadequate oral care behaviors. This study aims to determine the relationship between the behavior of diabetes mellitus patients and their oral hygiene status at Puskesmas Mutiara Barat, Pidie District. The research methodology employs a cross-sectional design with a sample of 40 diabetes mellitus patients visiting the Mutiara Barat Health Center in Pidie District. Data collection was conducted through interviews using a questionnaire and assessment of oral and dental hygiene status using the OHIS index. The research took place from March 8 to May 2 2024. The results showed that of the 40 respondents, 62.5% had poor behavior and 62.5% had poor oral and dental hygiene status. Bivariate analysis using the Chi-Square test indicated a significant relationship between the behavior of diabetes mellitus patients and their oral and dental hygiene status (p = 0.000). Poor behavior, such as not regularly maintaining oral hygiene, contributes to poor oral conditions in diabetes mellitus patients. The study concludes that there is a significant relationship between the behavior of diabetes mellitus patients and their oral and dental hygiene status. It is recommended that diabetes mellitus patients improve their oral hygiene habits, control blood sugar levels well, and regularly check their teeth. Health workers are expected to provide comprehensive and ongoing education on the importance of maintaining oral and dental hygiene for diabetes mellitus patients.